2014
DOI: 10.1007/s12639-014-0602-8
|View full text |Cite
|
Sign up to set email alerts
|

Study on impression smears of hepatic coccidiosis in rabbits

Abstract: Hepatic coccidiosis is a contagious and lethal disease condition in rabbits. The disease was recorded in six rabbits suffering with watery diarrhoea. Clinically, affected rabbits showed decreased growth rate, anorexia, debilitation, diarrhea and rough hair coat. Examination of the faecal samples revealed the presence of unsporulated oocysts of Eimeria spp. After sporulation Eimeria stiedae oocysts were identified. Postmortem examination revealed hepatomegaly with presence of discrete yellowish-white nodules on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 7 publications
4
18
0
Order By: Relevance
“…Impression smears from the intestinal mucosa also revealed the presence of many oocysts and merozoites along with the inflammatory cells especially macrophages and necrotic cells debris. The findings corroborate with the study on impression smear of hepatic coccidiosis in rabbits earlier reported by Sivajothi et al (2016).…”
Section: Cytologic Interpretationsupporting
confidence: 92%
“…Impression smears from the intestinal mucosa also revealed the presence of many oocysts and merozoites along with the inflammatory cells especially macrophages and necrotic cells debris. The findings corroborate with the study on impression smear of hepatic coccidiosis in rabbits earlier reported by Sivajothi et al (2016).…”
Section: Cytologic Interpretationsupporting
confidence: 92%
“…The livers and intestines from amprolium and trimethoprimsulfamethoxazole (potentiated sulphonamide) treatment groups had severe gross and microscopic lesions indicating their inability to treat clinical coccidiosis. Gross lesions in these groups were characterized by hepatomegaly, raised yellowish-white multinodular lesions, distended biliary tree filled with viscous to cheesy content, fibrinous strands on the liver surface, congested and hemorrhagic intestines with ballooned sections consistent with those described in previous studies [34,35]. Hyperplasia and cystic enlargement of the bile duct epithelium has been reported to results in the yellowish-white nodular lesions on the liver surface seen in our study [8,28].…”
Section: Effects Of Anticoccidial Drugs On Gross and Histopathologicasupporting
confidence: 88%
“…The obtained material was evaluated through macroscopic analysis of each liver and gall bladder and inspected for nodules typical characteristic of infection with Eimeria stiedae followed by liver smear treatment (Sivajothi et al 2014). Histopathologically, intestines of the dead rabbits were thoroughly examined for the gross lesions and specimens were collected in 10% formalin.…”
Section: Species Identificationmentioning
confidence: 99%